A Habitat Suitability Model for Capybara (Hydrochoerus Hydrochaeris) at Its Core Area in Argentina. (March 2015) - Schivo, Facundo; Kandus, Patricia; Bolkovic, María Luisa; Minotti, Priscilla Gail; Trilla, Gabriela González; Quintana, Rubén Darío
Habitat loss is one of the main factors reducing wildlife diversity and restricting its conservation. Habitat suitability models are important tools for wildlife management and conservation in order to evaluate the impacts of human activities on wildlife habitats. The capybara ( Hydrochoerus hydrochaeris ) is a semi-aquatic rodent that lives in South American wetlands that are subject to heavy human use. A spatially explicit model of capybara's Potential Habitat Suitability (PHS) was developed for the core area of its distribution in the humid subtropical region of Argentina. Predictive variables in this deductive model were related to capybara habitat requirements, and their values were obtained from existing published papers. The PHS model was performed using two data subsets that evaluated both ecological requirements and anthropogenic threats, resulting in two partial indices: Potential Ecological Suitability (PES), and Risk of Human Impact (RHI). The PES assesses vegetation cover and the presence of lentic and lotic freshwater bodies. The RHI estimates habitat fragmentation and accessibility of poachers. Variables for the habitat requirements were spatially expressed through Geographic Information Systems. The model accuracy assessment was performed through field work and achieved 72% of overall accuracy. Results indicate that 13% of the study area had the highest values of PHS index, characterized by the presence of vast wetlands, habitats with low fragmentation and low accessibility for poachers. These results are a useful tool to improve conservation and management programs for protection of capybara habitat.